Use of Artificial Intelligence as an Interactive Media for Students at Tigabinanga State High School - Nursamsiah, Nursamsiah; Sartika, Diah; Setiawan, Hasrian Rudi (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
Teachers must be able to design lessons that stimulate students' thinking by using innovative media in the current era of globalization, chief among them media based on artificial intelligence (AI) technology. This will be seen in the high school learning process, making AI-based media technology an aid in promoting students' creativity and intellectual growth. The use of innovative technology-based media in elementary school education is a diversion from the use of conventional text-based media. The application of AI in education will bring new perspectives and positive changes in teaching and learning as it will make teaching and learning easier for teachers and students in high schools. In this era of globalization, artificial intelligence (AI) media based on theory and information technology (IPTEK) is needed to increase student activity and academic performance in high school.